Prescribing pattern of antibiotics in pediatric wards of Bishoftu Hospital, East Ethiopia - Feleke, Mestawot; Yenet, Wubante; Lenjisa, Jimma Likisa (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Irrational use of antibiotics leads to emergency of resistant bacteria and hence infections that are even worse than the original diagnosed ones. So, appropriate drug utilization studies are found to be crucial to evaluate whether these drugs are properly used. For this reason, this study was designed to assess the overall antibiotics use practice in one of the largest government hospital’s pediatric ward in Ethiopia. Methods: A prospective study was carried out on 120 hospitalized patient’s selected using simple random sampling. Data had been analyzed by software called statistical package for social science (SPSS) version 16. Chi-square (X2) was used to test possible association between some variables. Results: In this study, the major disorders for which antibiotics were prescribed include pneumonia (56.3%) and acute gastroenteritis 9.40 %. The most commonly used antibiotics were Ceftriaxone and gentamicin which accounted for 43.5% and 25.6% respectively. Poly pharmacy was as high as 28.3% and it was highly associated with the length of hospital stay (p<0.01). Antibiotic prescribing in this hospital pediatric ward was purely empirical. Conclusion: In general, Ceftriaxone and gentamicin were identified to be the most commonly prescribed medications in this hospital. We would like to recommend that antibiotic selection should be based on culture and sensitivity test results. Cost of long term use of parenteral medications and shift to equivalent oral dose should be considered whenever possible.